Assessment of nutritional status of adolescent school going boys of Himachal Pradesh - Pathania, Neetu S.; Biswas, Rajib (International Journal Of Community Medicine And Public Health, 2021)
Background: Given the paucity of data on the nutritional standard of the Himachali children, the present study was conducted to assess the physical growth and malnutrition of adolescent school-going boys of Himachal Pradesh within the age group of 15-17 years. Methods: Boys were selected from both government and private schools of the non- hilly regions of Mandi district of Himachal Pradesh. Height, weight, and BMI were determined. Stunting was evaluated from height-for-age Z-score, and thinness, overweight, and obesity were estimated from BMI-for-age Z-score using the WHO recommended cut-off values. Results: Mean height varied between 167.2 to 168.7 cm. Weight varied between 52.4 to 56.1 kg with a corresponding BMI between 18.7 to 19.7 kg/m2.The overall prevalence of stunting and wasting were 5.7% and 15.8% respectively. The coexistence of stunting and wasting was not found in any of the age groups. The overall prevalence of overweight and obesity was 5.4% and 1.7% respectively. Conclusions: Himachali boys appeared to be taller than most of the Indian population of boys of similar age groups. Prevalence of the different categories of over nutrition and undernutrition were also lower as compared to that obtained for other Indian studies on adolescent boys. The existence of overweight and obese individuals points towards the double burden of malnutrition.